An Analysis of NTMs Measures on Indonesian Banana and Pineapple Exports in Selected Asean, East Asian, and Middle Eastern Countries - Zainuddin Zainuddin; Araz Meilin; Asmaida; Mulyani (Jurnal Manajemen dan Agribisnis, 2025)
Background: Increasing Indonesia's banana and pineapple exports is part of an effort to promote fresh and processed fruit. Banana and pineapple exports face several challenges, especially in conforming to food safety requirements in destination markets. Purpose: The objective is to describe Non-tariff measures (NTMs) measures (i.e.SPS and TBT), and their impact on Indonesian banana and pineapple exports. Design/methodology/approach: In this study, we analyze the effect and impact of NTMs measures using the gravity model by including the variable of NTMs measures. Findings/Result: This analysis finds that SPS measures have a trade-promoting impact on Indonesian banana and pineapple exports in export markets. In contrast, TBT measures have a trade-impeding impact on Indonesian banana and pineapple export. Ad valorem tariff-equivalents (AVEs) of SPS measures are higher than those of TBT. The AVEs of SPS measures are relatively higher than import tariffs in pineapple export markets. Food safety policies (i.e. SPS and TBT) are still more protective in the export markets of both commodities.Conclusion: Increasing Indonesia's banana and pineapple exports requires alignment and adjustment of NTMs in export markets. Increasing farmer partnerships with similar large companies to implement good production practices will help accelerate compliance with standards to improve market access.Originality/value (State of the art): This study specifically examines the impact of non-tariff measures on Indonesian bananas and pineapples in export markets and considers the magnitude of market barriers down to the 6-digit HS code level by measuring the tariff equivalent of NTMs barriers. Keywords: banana, non-tariff measures, pineapple, food safety, destination markets